إنتاج الهيدروجين باستخدام نظام محللة كهروشمسية ذات الغشاء التبادل البوليميري - علي علي; ناظم خرفان (Tishreen University, 2017)
إن إنتاج الهيدروجين، كمصدر حامل للطاقة، من خلال التحليل الكهربائي للماء يمكن أن يكون مجديا اقتصاديا باستخدام الطاقة الكهربائية من مصادر الطاقة المتجددة مثل الطاقة الشمسية. في هذا البحث تم دراسة إنتاج الهيدروجين الشمسي باستخدام محللة كهروشمسية تعتمد على تقانة غشاء التبادل البوليميري صنعت محليا في كلية الهندسة التقنية بطرطوس. الدراسات التجريبية تم إنجازها بطريقتين مختلفتين: الأولى الربط المباشر لمحللة الهيدروجين مع المنظومة الفوتو فولتية. الطريقة الثانية تم تصميم نظام لمحللة هيدروجين كهروشمسية يتكون من العناصر التالية: مجموعة PV، تعقب نقطة الطاقة القصوى (MPPT)، محول DC-DC، والذي يستخدم لتشغيل النظام على أقصى قدر من طاقة النظام الكهروضوئية في جميع الأوقات لتزويد المحللة بالتيار الكهربائي اللازم، خزان هيدروجين. أظهرت النتائج بان الطريقة الثانية اكثر فعالية وذات كفاءة عالية بالمقارنة مع الطريقة الأولى نظرا" لتغير شدة الإشعاع الشمسي خلال اليوم الواحد. تببن النتائج ايضا" أن بعض الإضافات مثل (KOH) يلعب دور مهم في تعزيز عملية التأين للسائل الكتروليتي وتحسين تدفق الهيدروجين. Hydrogen production, vector of energy, by water electrolysis can be economically viable by using electrical energy from renewable sources such as photovoltaic solar energy. In this research was the study of solar hydrogen production using electrolyser based on polymeric exchange membrane electrolysis technology manufactured locally at the Faculty of Technical Engineering in Tartous. The experimental studies were achieved in two different methods: the first, direct coupling to the hydrogen electrolyser with PV module. The second method, designed PV-electrolyzer system consists of the following components: PV module, a maximum power point tracker (MPPT), A DC-DC converter, which is used to operate the system at the maximum power of the PV system at all times and to supply the necessary DC current to the electrolyzer, and tank hydrogen. The results showed that the second method more effective and highly efficient when compared with the first method because of the change in the intensity of solar radiation during the day. Also, results show that some additives such as (KOH) play an important role in enhancing the ionization process of the electrolyte liquid and improve process flow